Avaliação do Efeito da Agitação e Mistura no Processo de Produção do Biodiesel de Mamona via Transesterificação Metílica - Nazário, Jaelson de Lima (2014)
Most part of the energy demand on the planet is derived from petroleum, a nonrenewable energy source that releases large amounts of greenhouse gases in the atmosphere. Many researches have been devoted to the development of renewable energy sources that are less agressive to the environment. Biodiesel is a renewable, non-toxic and less polluent fuel, thus being a potential alternative to mineral diesel. It is produced from vegetable oils or animal fats. The transformation of vegetable oil into biodiesel by transesterification reaction consisting of a reaction between triglyceride oil and a lower alcohol, usually methanol or ethanol. The soil and climate in BR is attractive to a diversity of oil plants that can be used in biodiesel production. Among them, it can mentioned the castor bean, which grows in regions with low rainfall, as the semi - arid northeastern region. This work aimed to study the effect of stirring and mixing in the production of biodiesel from castor oil via transesterification and methyl alkaline catalysis process. Stirring rate, molar ratio oil / alcohol, the impeller type, the reaction time, the temperature, presence or absence of baffles and catalyst type. Therefore, a fractional factorial design 27-2, having as variables was used. We initially determined the physicochemical properties of castor oil. The experiment was performed in duplicate, with the biodiesel yield in each reaction determined by gas chromatography. Separately the effects of binary variables and their interactions were analyzed, providing the preparation of the statistical model for the yield of biodiesel from castor beans. The best conditions for production of biodiesel from castor oil via transesterification methyl were: turbine impeller; without baffles, stirring speed of 500 rpm, molar ratio oil / alcohol 1:7, NaOH catalyst, reaction time of 30 min and temperature of 50ºC.